2018
DOI: 10.5539/jel.v7n3p219
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Teachers’ Self-Efficacy Beliefs, Locus of Control and Intercultural Sensitivities from the Perspective of Individual Differences

Abstract: The purpose of this study is to examine the correlation between Teachers' Self-efficacy beliefs, locus of control and intercultural sensitivities and to analyze these variables based on various demographic variables. The data of the study were collected through teachers’ locus of control scale developed by Sadowski, Taylor, Woodward, Peacher, & Martin (1982) adopted into Turkish by Buluş (2011), teachers’ self-efficacy beliefs scale developed by Dellinger, Bobbett, Olivier, & Ellet (2008) adopted into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Akkaya and Akyol (2016) found that teachers' perception of ILC is lower than their perception of LOC based on others and luck/faith. Akca et al (2018) tested relationships among self-efficacy beliefs, LOC, and intercultural sensitivities among teachers. They found a positive connection between the level of intercultural sensitivity and the level of LOC (R = 0.436, p < 0.01), and it can be concluded that the level of intercultural sensitivity was higher with individuals having a high level of LOC than with individuals having a low level of LOC.…”
Section: Loc In Education-oriented Professionsmentioning
confidence: 99%
“…Akkaya and Akyol (2016) found that teachers' perception of ILC is lower than their perception of LOC based on others and luck/faith. Akca et al (2018) tested relationships among self-efficacy beliefs, LOC, and intercultural sensitivities among teachers. They found a positive connection between the level of intercultural sensitivity and the level of LOC (R = 0.436, p < 0.01), and it can be concluded that the level of intercultural sensitivity was higher with individuals having a high level of LOC than with individuals having a low level of LOC.…”
Section: Loc In Education-oriented Professionsmentioning
confidence: 99%
“…This finding may be related to the greater predisposition of women and young people to the predominance of external locus of control (Çakir, 2017;Taş & İskender, 2018). In turn, this could justify that these sample subgroups perceive, in general, less self-efficacy in their teaching tasks (Akca et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Based 10.3389/fpsyg.2022.923874 on Rotter's (1966) classification, the LOC can be internal or external. People with an iLOC (i.e., internals) believe that they are responsible for everything (good or bad) happening in their lives (Levenson, 1974;Akca et al, 2018;Yuwono et al, 2020). Conversely, people with an external LOC (i.e., externals) believe that luck, external forces, or chances are responsible for events in their lives (Dagal and Bayındır, 2017;Yuwono et al, 2020).…”
Section: Moderating Role Of Internal Locus Of Controlmentioning
confidence: 99%